2021
DOI: 10.1002/adpr.202100137
|View full text |Cite
|
Sign up to set email alerts
|

Mn2+‐Doped CsPbI3 Nanocrystals for Perovskite Light‐Emitting Diodes with High Luminance and Improved Device Stability

Abstract: Cubic α‐CsPbI3 has promising applications in the optoelectronic field for its excellent properties. However, α‐CsPbI3 black phase is instable at room temperature and easily converts into nonluminescent yellow orthorhombic phase (δ‐CsPbI3). Herein, the stability of α‐CsPbI3 is significantly improved by incorporating Mn2+ dopants into the perovskite lattice. Mn2+: CsPbI3 has essentially the same crystal structure as the parent α‐CsPbI3, and Mn2+ doping can promote photoluminescence quantum yield (PLQY) from 55% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…In recent years, numerous methods, such as heat injection, ligand replication and reprecipitation, spin coating, microemulsion, as well as cutting-edge ultrasound, have been employed to prepare all-inorganic perovskite nanomaterials. Perovskite nanomaterials with different morphologies and sizes, such as zero-dimensional (0D) perovskite quantum dots, one-dimensional (1D) nanowires (NWs) or nanorods, , and two-dimensional (2D) nanoplates, have been devised and synthesized by regulating the experimental conditions, including temperature, reaction time, capping agents, ion ratios, and templates. Compared with 3D and 2D nanomaterials, 1D perovskite materials have a high specific surface area and powerful quantum confinement effect, thus enriching their unique optical and physical characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, numerous methods, such as heat injection, ligand replication and reprecipitation, spin coating, microemulsion, as well as cutting-edge ultrasound, have been employed to prepare all-inorganic perovskite nanomaterials. Perovskite nanomaterials with different morphologies and sizes, such as zero-dimensional (0D) perovskite quantum dots, one-dimensional (1D) nanowires (NWs) or nanorods, , and two-dimensional (2D) nanoplates, have been devised and synthesized by regulating the experimental conditions, including temperature, reaction time, capping agents, ion ratios, and templates. Compared with 3D and 2D nanomaterials, 1D perovskite materials have a high specific surface area and powerful quantum confinement effect, thus enriching their unique optical and physical characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…S2 †), which was due to the lattice shrinking by replacing Pb 2+ with small-sized Mn 2+ . 4,45,46 According to their PL spectra (Fig. 2b), these white lights consist of two complementary colors, skyblue (482 nm) and orange-red (610 nm), which are attributed to the band edge emission of CsPbBr 3 NPLs and the ionic emission of Mn 2+ , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Mn ion doping in semiconductor materials not only results in new luminescence peaks, which are generated by energy transfer from the host to Mn ions, but also reduces the density of defect states and improves the PLQY and stability. 33–37 Therefore, metal halide perovskites with Mn ion doping have become a hot research topic. For example, David Parobek et al 38 reported Mn-doped CsPbCl 3 and CsPb(Cl/Br) 3 NCs, showing strong sensitized Mn luminescence.…”
Section: Introductionmentioning
confidence: 99%